Building a local spatial data infrastructure (SDI) to collect, manage and deliver coastal information - Conti, Luis Americo; Fonseca Filho, Homero; Turra, Alexander; Amaral, A. Cecilia Z. (Ocean & coastal management, 2018)
Mapping techniques and spatial data management in coastal areas are still the subject of methodological and technological development, especially regarding systems for the organization and integration of data and information. The availability of integrated and comprehensive spatial information within the context of a multidisciplinary project is therefore an important step towards to defining methodological solutions to the characterization of coastal environment and their interrelations for management. The “Biota/Araçá Project” (Biodiversity and functioning of a subtropical coastal ecosystem: subsidies for integrated management) is a multi-disciplinary program of biodiversity assessment of a small bay in Sao Paulo coast (Brazil). This paper discuss the issues involved in establishing a local spatial data infrastructure (SDI) developed to allow access, model and sharing of spatial data within such collaborative and multidisciplinary research project context. •Organization of structured multi-information systems is often driven by regional, national or multinational initiatives while detailed projects can be can clearly benefit from initiatives focused on local SDI structure.•Spatial Data models needs to be implemented in an interdisciplinary and collaborative way.•Geo Web tools increase awareness of existing opportunities for the availability of coastal and marine data among scientists and managers.